If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 8x + -13 Reorder the terms: -2 + 4x = 8x + -13 Reorder the terms: -2 + 4x = -13 + 8x Solving -2 + 4x = -13 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + 4x + -8x = -13 + 8x + -8x Combine like terms: 4x + -8x = -4x -2 + -4x = -13 + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + -4x = -13 + 0 -2 + -4x = -13 Add '2' to each side of the equation. -2 + 2 + -4x = -13 + 2 Combine like terms: -2 + 2 = 0 0 + -4x = -13 + 2 -4x = -13 + 2 Combine like terms: -13 + 2 = -11 -4x = -11 Divide each side by '-4'. x = 2.75 Simplifying x = 2.75
| 6x-2-8x+3=40x+8 | | -148=3(7x-8)+2 | | 7x/3=11 | | log(2x-1)-log(x-1)=x | | (5x-3)-(2x+1)= | | 450x-8000=720x-13000 | | -9(3m-9n+5p)= | | 2.5x-10=h | | 5m+7m-13=15m | | 2x+3x-7x= | | (a+b^2)=a^2+2ab+b^2 | | -8-2(3-9)=0 | | (-3x+2)+(5x-1)= | | ((5x)/4)-(1/5)=1-(2/5)(x-(1/10)) | | -113=-7(-2x+3) | | (X^2-5x+4)(x^2+7x-3)= | | 15x+10+5x=8 | | (5-3x)+(2x+4)= | | .75x-.2x+.8=5x | | 2x+3-4= | | 4x^2-21xy-25y^2=0 | | 36=.44*w | | 3x+5x+15=10 | | X(5x-2)+x(2x-3)=(7x+8)(x-3) | | (3+4x)+(x-2)= | | 36=.43*w | | 100(15t+4.75)=143.25 | | fx=4cos(2x) | | B=12.89+-8s | | ((5x)/2)-9=(2x-7)/6 | | (2x+5)(x^2-4x+3)= | | X^3-18x^2+78x-7=0 |